Answer:
You have the right answer
Step-by-step explanation
Equation 1) x + 6y = 2
Equation 2) 5x + 4y = 36
Multiply all of equation 1 by 5.
1) 5(x + 6y = 2)
Simplify.
1) 5x + 30y = 10
2) 5x + 4y = 36
Subtract equations from one another.
26y = -26
Divide both sides by 26.
y = -1
Plug in -1 for y in the first equation.
x + 6y = 2
x + 6(-1) = 2
Simplify.
x - 6 = 2
Add 6 to both sides.
x = 8
D : (8, -1)
~Hope I helped!~
Answer:(3x+7)(x+2)
Step-by-step explanation:
Answer: = −9
Step-by-step explanation:
Answer: b) two sides and the included angle are congruent
<u>Step-by-step explanation:</u>
RS = QS SIDES are congruent
∠PSR ≡ ∠PSQ ANGLES are congruent
PS = PS SIDES are congruent
ΔPSR ≡ ΔPSQ by the Side-Angle-Side (SAS) Congruency Theorem
Since we know the triangles are congruent, we can state that their parts are congruent:
Congruent-Parts of-Congruent-Triangles are-Congruent (CPCTC)